MARSILEA QUADRIFOLIA LINN. - A VALUABLE CULINARY AND REMEDIAL FERN IN JADUGUDA, JHARKHAND, INDIA: Life Science-Plant Ecology - SONI, PRAFULLA; SINGH, LAL (International Journal of Life Science and Pharma Research, 2012)
An investigation has been made on the relevance of one such lesser known species Marsilea quadrifolia Linn. (Vernacular name - sushni saag) commonly used by ‘Ho’ tribes in the mining belt of Jaduguda, Jharkhand (India) for its culinary and medicinal properties. Besides exploring indigenous knowledge of local tribals, the study also incorporates the survey of local markets in and around Jaduguda. Information was collected from the local tribal people (Ho) as well as local drug sellers in the Haat (local market) pertaining to use of Marsilea quadrifolia Linn. It is a pteridophytic plant that is marketed and used by tribals of that area for its nerve relaxant nature and curative properties for various other ailments of nervous system and its nutritional value. The present paper compiles botanical description of M. quadrifolia Linn., its traditional folk medicinal uses and marketing and monetary benefit to the villagers.